Fending Off Unverified Accusation with Narratives: The Role of Primary and Secondary Narratives in Organization’s Response Effectiveness in an Ongoing Crisis (Journal of International Crisis and Risk Communication Research, 2023)
This study integrates theories of metanarration and crisis narratives to identify optimal approaches to managing uncertain and high-pressure crisis situations. An online experiment used a U.S. adult sample to examine how (1) the primary narrative in a news story about the victim and (2) the secondary narrative with different crisis narratives used by the accused organization impacted the outcomes of the organization’s public communication about the ongoing crisis situation. Results showed that the secondary narrative, emphasizing renewal, played a significant role in (1) lowering perceived organizational crisis responsibility, (2) lessening organizational reputation damage, and (3) boosting supportive intention toward the organization. In addition, findings revealed that perceived organizational crisis responsibility and perceived organizational reputation functioned as sequential mediators for the relationshipbetween the secondary narrative (using renewal crisis narrative) and participants’ intended support of the crisis-stricken organization. Findings advance crisis narrative theory and offer prescriptions for effective and ethical organizational responses in managing an ongoing crisis triggered by an unverified sexual harassment accusation against its members.